A 'Pratyahaar' (A Dialogue with Mind and its Withdrawal) for Mental Health Care in writing of Marathi Spiritual Leaders - Rajshree Chitale; Aruna Jadeja (Dr. Chinmay Pandya, 2022)
Practice of keeping mind peaceful is done with the yoga, an ancient practice, where mind can be trained more focused. Ashtang Yoga by Pantajali follows Yam, Niyam, Aasan, Pranayam, Pratyahaar, Dharna, Dhyan, Samadhi. Here would like to connect Pratyahaar with mind. Pratyahaar is withdrawal of the senses. Mind can be satisfied with explanations. Psychologists discuss with any aspirant who is starving for peace. Brain is important organ of human body at the same time mind resides somewhere near by it. Human mind is creating main six emotions. Happiness, sadness, fear, humiliation, amaze and anger. These six emotions are responsible to create memories and even experiences. They are direct or indirect reason behind one's behaviour. It is a natural process when such emotions develop with the response of human body. Many a times because of the nature or tendency and circumstances one supresses those emotions. When this suppression happens repeatedly one can feel it's adverse effects on physical and mental health. For that one need to control and manage such emotions. Maharashtra is a rich state for sages or saint Parampara. Spirituality and philosophy explained mainly by Panchratna (five gems) saint Gyaneshwar, saint Namdev, saint Eknath, saint Tukaram and Samarth Ramdas. It is a regular practice in Maharashtrian culture and homes to chant creation of these saints. Mind where emotions and thoughts arise. Verses and teachings by Panchratnas are ways by which one can directly talk and motivate mind. It is just hammering mind to do withdrawal of thoughts and reaching to a state of peace of mind. Where emotions can be managed and controlled without supressing them. This can turn as an alternative therapy which is walking together with spirituality.